Analyzing effects of interfaces on recovery rates of shape memory composites from the perspective of molecular motions. (28th July 2018) - Chen, Hairong; Xia, Hong; Qiu, Yiping; Ni, Qing-Qing
Abstract: Over recent years, researchers have noticed that recovery rates of shape memory composites (SMCs) would vary due to the addition of fillers. So far, although several superficial reasons are discussed, a thorough analysis has not been presented yet probably due to the absence of a microscopic mechanism of SMCs. Here, a molecular mechanism of SMCs is clarified by identifying the differences lying in molecular motions of shape memory polymers and SMCs. On the basis of the molecular mechanism of SMCs, both a positive effect and a negative effect of fillers on recovery rates are revealed. Because interfaces between fillers and matrices play a decisive role in the two effects of fillers, several experiments are designed to verify the role of interfaces. The experimental results prove that the interfaces are benefit and harmful for recovery rates at the same time. Moreover, the results are able to qualitatively predict that the recovery rates of SMCs would increase or decrease with more addition of fillers.